If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.375x + 4 = 0.66 Reorder the terms: 4 + 0.375x = 0.66 Solving 4 + 0.375x = 0.66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 0.375x = 0.66 + -4 Combine like terms: 4 + -4 = 0 0 + 0.375x = 0.66 + -4 0.375x = 0.66 + -4 Combine like terms: 0.66 + -4 = -3.34 0.375x = -3.34 Divide each side by '0.375'. x = -8.906666667 Simplifying x = -8.906666667
| -6+3k=4k-8 | | 6x-18=2x+12 | | 6(4v+2)=36 | | 1/9m-3=0 | | 5x+7y-4z=31 | | -x-11/3=21 | | (2x+40)+(5x+12)= | | w-4w-32=0 | | 4t=21 | | 2p^2+2p-9=0 | | 2x-y-1=o | | 0.045=x | | 0.5x-3=0.8 | | 2(x+2)-6=5x+1 | | 9k-2k+3k-6k=12 | | x-75/7.5=y | | 2(2w+7)=2w+7 | | y=.33(9x-18) | | 2a+7a+13a+(-5a)-15a-4=-10 | | 6=1/12x | | 3x-14/4=x-8 | | 5x+35=13x-5 | | 6x=12.24 | | 0.166x+2=0.33 | | 3x+(2x-6)=91.50 | | X-3(x-2)=7x-1(2x+5) | | -16x^2+44x+18=0 | | X(x+3x)=28 | | 2(4b+8)=4+6b | | 3t-(-12t)-15t+(-20t)-(-8)=-12 | | -5(1-(-25))+5((-8(-5))-2)=-4(-5)-8(-5) | | 0.25x-3=0.4 |